2007
DOI: 10.1007/s11136-007-9250-0
|View full text |Cite
|
Sign up to set email alerts
|

Loneliness and health-related quality of life for the empty nest elderly in the rural area of a mountainous county in China

Abstract: Reducing the level of loneliness may be helpful to improve the quality of life for the empty nest elders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

18
196
3
5

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 190 publications
(222 citation statements)
references
References 15 publications
18
196
3
5
Order By: Relevance
“…This finding also correlates with previous findings (McDougall et al, 1997;Wei, 2004;Liu and Guo, 2007). The study gave the participants a chance to interact with people rather than remaining alone for the whole time.…”
Section: Improvement In the Feeling Of Lonelinesssupporting
confidence: 91%
See 2 more Smart Citations
“…This finding also correlates with previous findings (McDougall et al, 1997;Wei, 2004;Liu and Guo, 2007). The study gave the participants a chance to interact with people rather than remaining alone for the whole time.…”
Section: Improvement In the Feeling Of Lonelinesssupporting
confidence: 91%
“…Research on the association between reminiscence and loneliness remains limited, however, some studies have demonstrated a decrease in the feeling of loneliness when reminiscence therapy was provided 1-3 times per week for at least 1 h, occurring between 10 and 13 sessions. The UCLA Loneliness Scale was commonly used in these type of studies (McDougall et al, 1997;Wei, 2004;Liu and Guo, 2007). According to these study results, reminiscence eased the feeling of loneliness among the elderly, with the average score of the UCLA Loneliness Scale dropping from 44.9-54.2 to 35.5-40.4 ( p < .05) (McDougall et al, 1997;Wei, 2004;Liu and Guo, 2007).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…The positive factors are better access to health services, education, financial and social services. Individual and family mobility make it easier to escape from the loneliness and depression [5]. However, life in urban areas seems to lead to larger inequalities among population groups in regard to urban-rural differences in distribution of risk factors from disease, morbidity and mortality from cardiovascular disease [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Nessa fase, também são observados sintomas de depressão, dependência e desestruturação familiar, como é o caso da assim chamada síndrome do ninho vazio, que foi definida em algumas culturas como o sofrimento associado à perda do papel da função parental com a saída dos filhos da casa dos pais [3][4][5][6][7][8][9] . Barber 10 , em 1989, descreveu o termo ninho vazio como o período compreendido entre o momento em que o último filho que deixa a casa e aquele em que ocorre a morte de um dos parceiros.…”
unclassified